Prevalence of Multidrug Resistance in Pseudomonas Aeruginosa in Healthcare Facilities - Maria Muddassir, Almas Raza, Sadaf Munir, U. Basirat, O. Arshad Dar, Mazia Shahid, S. Shoaib Ahmed, S. Shamim, S. Z. H. Naqvi (Pakistan Journal of Medical & Health Sciences, 2022)
Pseudomonas aeruginosa is on the list of Gram-negative pathogens that are increasingly being counted as significant causes of nosocomial infections leading to significantly raised levels of morbidity and mortality. Life-threatening infections become more debilitating for those having a compromised immunity. The importance of Pseudomonas aeruginosa as a disease-causing microbe is enhanced through its increasing resistance to antibiotic drugs, the virulence factors plus its strength to adapt to wider environmental conditions. Pseudomonas aeruginosa possesses multiple acquired and intrinsic mechanisms providing resistance, often with augmented rates of resistance to multiple antimicrobial drugs. In the last decade, the global dissemination of the presumed ‘hazardous clones’ of multiple drug-resistant and extensively drug-resistant Pseudomonas aeruginosa have emerged as a serious threat to communal healthcare requiring extensive study and should be managed with determination and urgency. From the list of infections that are due to Gram-negative bacteria, Pseudomonas aeruginosa counts as a leading microbe causative for health-care-related infections in hospitalized individuals. In accordance with the guidelines by WHO, certain measures adopted in healthcare settings can help prevent transmission of multidrug-resistant Pseudomonas aeruginosa including hand hygiene (using alcohol-based solutions), contact precautions, cleanliness of the environment, isolation of patient (cohort or single room), plus surveillance. Keywords: Antibiotic resistance, Nosocomial, Infections, Resistance mechanisms, Pseudomonas aeruginosa